PENAFSIRAN DENGAN MENDIALOGKAN SASTRA JAWA DAN BALAGAH DALAM TAFSIR FAIḌ AL-RAḤMĀN : Studi QS. Al-Baqarah/2:261 - Panggih Widodo, Widodo; Muhammad Hariyadi, Hariyadi (Institut Agama Islam Sumatera Barat, 2025)
This study examines the interpretation of QS. al-Baqarah/2:261 in the tafsir Faiḍ al-Raḥmān through a dialogical strategy that intertwines Javanese literature and the science of Balāghah in its exegesis. It analyzes the expertise and uniqueness of K.H. Shaleh Darat in integrating Javanese literary elements with Balāghah within his interpretation of the verse an aspect that has not been thoroughly explored in previous research. This is a library-based study, with primary data consisting of QS. al-Baqarah/2:261 and the tafsir Faiḍ al-Raḥmān, while secondary data includes classical texts, books, and scholarly journals relevant to the research theme. The study employs interpretive, cultural, and linguistic approaches. The interpretation of QS. al-Baqarah/2:261 in the tafsir Faiḍ al-Raḥmān book seems to maintain the Balagah elements contained in the verse even though it is interpreted using Javanese. This can be seen from the interpretation of the verse which uses the Arabic Pegon script, Krama Madya Javanese, certain typical words in Javanese, and the Pepindhan style of language. The use of several of these things shows the ability of the author of the tafseer book in dialoguing the Balagah elements of the verse with Javanese literature, so that the literary beauty contained in the verse of the Qur'an is not lost even though it is interpreted in a language other than Arabic. In addition, it can also maintain the existence of Javanese literature.